Arduino-based Charity Box Safety, Tracking, and Counter System - Tri Raharjo Yudantoro; Liliek Triyono; Dwi Desy Nur Hani'ah; Moudina Risma Slodia (JAICT, 2019)
The charity box is a supporting facility that can be used by pilgrims to distribute their infaq. In this modern era, it turns out that the mosque still counts the contents of the charity box manually and uses the usual padlock key for the safety of the charity box. The purpose of this research is to build a system and tool that can simplify the performance of mosque administrators in counting money and maintaining the security of the charity box. ArduinoBased Charity Box Safety, Tracking, and Counter System is a charity box equipped with automatic counting and security features using RFID and GPS. The method used in making this system is the waterfall method. The features in this system are automatic counting and security features using RFID keys, GPS, buzzers, and infrared sensors. This system is also equipped with a notification to the mosque management regarding the amount of money in the charity box and the location of the charity box using GSM / GPRS. From the testing of the system, it was produced that the Arduino-Based Charity Box Safety, Tracing, and Counter System was able to detect banknotes and coins well. The SMS feature also works well where there will be an SMS message regarding the amount of money and location of the charity box. The safety of the charity box is enhanced by using RFID, GPS, buzzers, and infrared sensors. From the user satisfaction test results obtained by the percentage of user satisfaction by 85%, which means the Arduino-Based Charity Box Safety, Tracing, and Counter System is quite attractive to users.